Do not open wide; accidentally swallowed dental mold causing bowel obstruction. A case report. Issue 9 (14th September 2022) - Negrete, Jose R; Carrillo, Marco D; Molina, Gabriel A; Ayala O, Andres V; Flores, Daniel; Castillo, Daniel
Abstract: Foreign body ingestion is a common condition in daily practice; fortunately, most cases do not require endoscopic or surgical treatment, as most foreign bodies pass through the intestine without injuring it. Although mainly seen in children, adults can also be affected, especially in accidental situations and suicide attempts. Therefore, the clinical history and the environment in which the event occurred are essential for a rapid diagnosis. This can be even more challenging as most adult patients are rarely aware of ingestion. Therefore, a high index of suspicion is necessary. Therapy will depend on the foreign body's size, shape and material; treatment should not be delayed if complications are detected. We present a case of a 34-year-old man who accidentally swallowed the mold of his teeth while undergoing a dental procedure. Subsequently, he presented with an intestinal obstruction that required surgery. Fortunately, he made a full recovery.